STRATEGI PEMASARAN DI ERA DIGITAL DENGAN MENERAPKAN BERBISNIS SECARA ISLAM (STUDI USAHA GROSIR AL-MASHDUQIAH) - Siti Aisyah (IZZI: Jurnal Ekonomi Islam, 2024)
This research aims to find out and analyze how marketing concepts and strategies in the digital era and Islamic business are implemented by the Al-Mashduqiah Wholesale shop business unit located on Jl. Juanda No. 370, RT.01, Kp. Arabic, Benchmark, District. Kraksaan, Kab. Probolinggo The aim of this research is to find out and analyze Marketing Strategy from an Islamic Business Perspective, Al-Mashduqiah Wholesale Shop Business Study. and how to implement it for micro, small and medium enterprises and small and medium enterprises so that it is hoped that the resume results from this research can be used as a framework or model for other business actors. This research uses descriptive research and uses field studies and analyzes concepts carried out by Al-Mashduqiah Wholesale shop entrepreneurs. The results of this research indicate that the marketing strategy carried out by the wholesale shop business unit is to do business according to Islamic sharia in the micro, small and medium wholesale shop business sector. The results show that the Al-Mashduqiah Wholesale shop business belongs to the Islamic boarding school business unit located in the Patoan Arab Village Islamic boarding school, Kec. Kraksaan applies good Islamic business behavior from entrepreneurs to be applied in his business sector. In implementing marketing strategy activities, wholesale shop business actors have understood and implemented Islamic principles or values ​​based on the sources of the Al-Qur'an and Hadith.